Analisis Kinerja Pembuatan dan Perancangan Amplifier (Penguat Suara) Pada Sound System di PT Fastrobotic Bantul Yogyakarta - Febriyanto, Dionisius; Rahmadewi, Reni (Jurnal Ilmiah Wahana Pendidikan, 2024)
A sound system is a system used to generate and amplify sound in a variety of applications, such as music concerts, theatrical stages, and home audio systems. One of the important components in a sound system is an amplifier or system amplifier, whose job is to amplify the audio signal so that it can drive speakers with good sound quality. This study aims to perform performance analysis in the manufacture and design of amplifiers on sound systems. The method used includes component selection, circuit design, and testing the performance of the amplifier being built. At the manufacturing stage, the components used are selected based on the desired specifications, including the types of transistors, capacitors, and resistors. The amplifier circuit is then designed based on the principles of electronics and the desired design. The results of the performance analysis can be used to improve the amplifier design, make component adjustments, or choose a better alternative. In addition, performance analysis also provides a better understanding of the characteristics of the amplifier in producing sound quality.